2020
DOI: 10.1155/2020/2943848
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Atrophy in Systemic Lupus Erythematosus Patients without Major Neuropsychiatric Manifestations

Abstract: This study was conducted to explore hippocampal structural changes and their possible associations with clinical characteristics, emotional status, and treatment regimens in patients with systemic lupus erythematosus (SLE) without major neuropsychiatric manifestations (non-NPSLE). Eighty-five non-NPSLE patients with normal conventional magnetic resonance imaging (MRI) and seventy-seven matched healthy control (HC) subjects were recruited. All participants underwent the standard high-resolution volumetric MRI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Cognitive dysfunction in NPSLE has been frequently associated with hippocampal functional changes [21][22][23][24][25][26]. Previously, we presented data of gene expression analysis in the cortex of MRL/lpr, Fn14ko, and MRL/+ mice [20].…”
Section: Phenotype-dependent Cortex-hippocampus Synchronous Expression Of Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive dysfunction in NPSLE has been frequently associated with hippocampal functional changes [21][22][23][24][25][26]. Previously, we presented data of gene expression analysis in the cortex of MRL/lpr, Fn14ko, and MRL/+ mice [20].…”
Section: Phenotype-dependent Cortex-hippocampus Synchronous Expression Of Genesmentioning
confidence: 99%
“…To further examine and validate the importance of these pathways, we proceeded to analyze the transcriptome of the cells in the hippocampus of the MRL/lpr mice compared with Fn14ko and background controls. The hippocampus has for long been implicated as a critical focus of neurocognitive and mood manifestation of NPSLE [21][22][23][24][25][26]. Thus, a careful analysis of its transcriptome may provide more specific and pertinent information regarding critical pathways in NPSLE, thereby identifying potential diagnostic markers, as well as promising treatment targets.…”
Section: Introductionmentioning
confidence: 99%
“…These volumetric differences are consistent with previously reported findings from individual studies and indicate both white matter and gray matter involvement. [26, 29, 33] When comparing patients with NPSLE to controls there was no significant difference in total gray matter volume.…”
Section: Discussionmentioning
confidence: 92%
“…Some observational studies have found an association between brain MRI abnormalities in NPSLE and low serum levels of C3 and C4 [ 14 - 15 ]. Liu et al explored the effect of brain atrophy on NPSLE and found a relationship between hippocampal atrophy and the development of neuropsychiatric manifestations and lupus-related organ damage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%